Wikipedia editing and information literacy: a case study. Issue 1 (9th January 2017) - Dawe, Lydia; Robinson, Ainslie
Abstract : Purpose: This paper aims to evaluate the success of a Wikipedia editing assessment designed to improve the information literacy skills of a cohort of first-year undergraduate health sciences students. Design/methodology/approach: In this action research case study (known hereafter as "the project" to differentiate this action research from the students' own research), students researched, wrote and published Wikipedia articles on Australia-centric health topics. Students were given a pre- and post-test to assess levels of self-confidence in finding, evaluating and referencing information. Student work was also analysed in terms of article length and quantity and the type of information sources used. Findings: Tests revealed that students' self-confidence in their information literacy skills improved overall. Analysis of student work revealed that students wrote longer articles and incorporated more references than expected. References used were of appropriate quality relevant to the article despite minimal instructions. Originality/value: There are few studies that investigate information literacy development through Wikipedia editing in Australian universities. This study shows that Wikipedia editing is an effective way to carry out student assessment prior to essay writing and an innovative platform to improve information literacy skills in undergraduate students.